Mechanical occlusion of the transverse colon due to submucosal lipoma - Ríos Bruno, Guaymirán; Gateño Yaffe, Nisso; Maman, Perla (Cirugía del Uruguay, 1972)
In one patient mecanic occusion of the colon was caused by a submucous lipoma. They are rare in this location, and this type of complication is even more so.